2012
DOI: 10.1039/c1dt11293g
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures, and magnetic characterizations of cyanide-bridged FeIIIMnIIIchains constructed by mer-Fe(iii)tricyanide and Mn(iii) Schiff bases: Magnetostructural relationship

Abstract: Five Fe(III)Mn(III) bimetallic compounds [Fe(iqc)(CN)(3)][Mn(5-Xsalen)]·pMeOH·qMeCN·rH(2)O [Hiqc = N-(quinolin-8-yl)isoquinoline-1-carboxamide; salen = N,N'-ethylenebis(salicylideneiminato) dianion; X = H(2), F(3, 3a), Cl(4), Br(5)] were prepared by assembling a newly designed mer-Fe tricyanide (Ph(4)P)[Fe(iqc)(CN)(3)]·0.5H(2)O (1) and the respective Mn Schiff bases Mn(5-Xsalen)(+). Compounds 2-4 show linear chain structures in which trans-positioned cyanides of the Fe precursor bridge neighbouring Mn atoms, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 100 publications
3
18
0
Order By: Relevance
“…In recent years, much work has been carried out on the syntheses and properties of Schiff bases and their complexes [1][2][3][4][5]. You and co workers have prepared some Schiff base complexes with solvolthermal method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much work has been carried out on the syntheses and properties of Schiff bases and their complexes [1][2][3][4][5]. You and co workers have prepared some Schiff base complexes with solvolthermal method [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…1b (1), H(4)···N(12) iii 2.68 (3), N(4)···N(12) iii 3.559(9) Å, N(4)-H(4)···N (12) iii 163(6)°; symmetry codes: ii 1 -x, 1 -y, -1 -z; iii 3/2 + x, -1/2 -y, z), forming a 3D network (Fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, much work has been carried out on the syntheses and properties of Schiff bases and their complexes [1][2][3][4][5]. Schiff bases derived from salicylaldehyde and primary amines con stitute one of the most relevant synthetic ligand sys tems with importance in asymmetric catalysis and they appear to be of importance for a broad range of transition metal catalyzed reactions including lactide polymerization, epoxidation of olefins, hydroxylation and asymmetric ring opening of epoxides [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many 0D discrete clusters and 1D infinite coordination polymers have been successfully obtained by assembling the decorated polycyanometallates such as the blocked trans -dicyano-, fac -tricyano-, mer -tricyano- and tetracyanometallate, and the paramagnetic compound with or without the auxiliary ligand [18,19,20,21,22,23]. Several reports from our and other groups on the mer -[Fe(L](CN) 3 ] -/2- -based cyanide-bridged complexes, where L represents the equatorial in-plane ligands with relative large steric effect for efficiently lowering the dimensionality of the target complex such as bis (2-pyridylcarbonyl)amidate (bpca) [24,25], 8-(pyridine-2-carboxamido)quinoline (pcq) [26,27,28], 8-(pyrazine-2-carboxamido)quinoline (pzcq) [29], 8-(5-methylpyrazine-2-carboxamido)quinoline (mpzcq) [30], 8-(2-quinoline-2-carboxamido)quinoline (qcq) [31], N -(quinolin-8-yl)isoquinoline-1-carboxamide anion (iqc) [32], and bis (2-benzimidazolyl)pyridine (bbp) [33,34] showed that the mer -[Fe(L](CN) 3 ] -/2- type precursors are excellent candidates for constructing interesting magnetic assemblies. Here, a new structurally characterized mer -tricyanoiron(III) building block 1 (Scheme 1) was first employed to assemble with the manganese Schiff base compounds (Scheme 1), leading to a series of new CN-bridged Fe(III)-Mn(III) complexes with various structural types formulated as {[Fe(qxcq)(CN) 3 ][Mn(L 1 )(H 2 O)]}[Mn(L 1 )(H 2 O)(CH 3 OH)](ClO 4 )·1.5MeOH·0.5H 2 O (L 1 = N,N′-bis (3-methoxy-5-bromosalicylideneiminate) (2), {[Fe(qxcq)(CN) 3 ][Mn(L 2 )]} 2 ·0.5H 2 O (L 2 = N,N′ -ethylene- bis (3-ethoxysalicylideneiminate)) (3), [Fe(qxcq)(CN) 3 ][Mn(L 3 )] (L 3 = bis (acetylacetonato)ethylenediimine) (4), and [Fe(qxcq)(CN) 3 ][Mn(L 4 )]·1.5MeOH·0.5CH 3 CN·0.25H 2 O (L 4 = N,N′ -(1,1,2,2-tetramethylethylene)bis(salicylideneiminate)) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%